CAREGIVER IDENTITY THEORY AND PREDICTORS OF BURDEN AND DEPRESSION: FINDINGS FROM THE REACH II STUDY. (16th November 2018) - Miller, V; Killian, M; Fields, N
Abstract: Due to the degenerative nature of Alzheimer's disease (AD), caregivers (CGs) of persons with dementia face many challenges. CGs are often subject to stressors, placing them at a greater risk for depression and other mental health problems. Guided by the caregiver identity theory, we examine the relationship between care recipient's ability to perform daily tasks, ADLs and IADLs, and CG depression as mediated by CGs' perceived burden while caregiving for one with AD. Using baseline data from the REACH II study, relationships between burden, reported depression, and each ADLs and IADLs were tested. To explore CG burden mediating the relationship between and depression each ADLs and IADLs, structural equation modeling (SEM) was conducted. Reported CG total scores were significantly correlated with total ADLs (Spearman's rho ρ =.524, p<.001) and IADLs ( ρ =.495, p<.001) scores, indicating increased perceived CG burden with greater number of assisted daily activities. CG depression scores were significantly predicted by burden scores ( β =0.386, t=18.27, p<.001, r2=.346) and CG's ability to pay for basic needs ( β =1.10, t=4.50, p<.001, r2=.031). SEM modeling indicated that CG burden fully mediated the relationship between ADLs and IADLs and CG depression after controlling for CG's ability to pay for basic care needs. Our results shed light on the relationship between a CG's perceived burden and depression. Findings suggest the need to closely examine the relationships between AD caregiving, CG burden, and mental health. Results suggest bolstering policies and programs that offer tangible supports and services to ameliorate CG burden of informal AD caregiving.